Increasing the Role of Posyandu cadres by Processing Temulawak Milk Candy (Sutela) in an Attempt to Raise Children's Appetite in Support of Improved Nutrition for Children in Sukamulya Village - Marini Marini; Nourma Nurjanah; Azmi Darotulmutmainnah; Sukmawati Sukmawati; Herliningsih Herliningsih; Nova Oktavia; Nur Azizah (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The role of cadres is very much needed in posyandu services, apart from being tasked with providing education to parents regarding the importance of providing adequate and balanced nutritional intake but also helping to monitor the nutritional. One plant that can help kids eat more is Temulawak; its curcuminoid content and essential oils can support the function of the pancreas and bile to improve food absorption in the intestines; additionally, the nutrients in pure milk are critical for the development of healthy bones and teeth, so feeding kids this combination can help them eat better. This community service aims to increase the role of posyandu cadres through training activities on processing medicinal plants into temulawak milk candy (Sutela) in an effort to increase children's appetite. The method used is in the form of counseling and training for posyandu cadres on how to process ginger and pure milk plants into silk candy in Sukamulya Village. As a tool to ensure the achievement of this service activity, an assessment is carried out using a questionnaire before the counseling begins to measure participants' initial knowledge and after the counseling to evaluate the extent to which participants' understanding and knowledge have increased after participating. The result of this community service is that posyandu cadre participants enthusiastically took part in this activity, this can be seen from the number of participants who attended, namely 90% and increased knowledge of participants relating to counseling and training materials delivered before and after the activity, namely before the activity by 30,8% and after by 95,4%. In conclusion, there is an increase in the theoretical understanding and skills of posyandu cadres regarding the processing of temulawak milk candy which is beneficial for children's health in Sukamulya Village.